Genetic diversity analysis of Linseed (Linum usitatissimum L.) accessions using RAPD Markers - Nagabhushanam, Beema; Mir, Mohammad Imran; Nagaraju, M.; Sujatha, E.; Devi, B. Rama; Kumar, B. Kiran (Emirates Journal of Food and Agriculture, 2021)
It is important to analyse the degree of genetic variation existing within the genome to extend the genetic base of linseed/flaxseed accessions in order to preserve, evaluate and use genetic resources accurately and successfully. The main aim of the current investigation was to evaluate the scope and spread of genomic variation across different linseed accessions by employing molecular markers (RAPD). The genomic DNA of 12 linseed accessions was amplified with 16 decamer RAPD primers that generated 81 total bands, among which 75 bands were polymorphic and 6 bands were monomorphic. Polymorphic band numbers varied from least 2 (OPS-11) to highest 10 (OPS-07). The magnitude of polymorphism ranged from 75% to 100% among all accessions with a mean of 93.15 % across all the accessions. The value of Polymorphic Information Content (PIC) varied from 0.133% to 0.708% with a mean of 0.45% for each primer. The maximum PIC value (0.708) was found with the primer OPS-07 and (0.702) with OPM-13. The primer OPS-03 showed the minimum PIC value (0.133). Two main different clusters -I and -II were seen in the cluster analysis depending on RAPD data. Cluster-II comprises one accession (IC 564585) that was the highly varied accession, whereas Cluster-I comprises of some sub clusters with all the remaining accessions. The Jaccard's similarity coefficient varied from 8.2 to 96.3%. The accessions BHU-A and BHU-B had the highest genetic similarity (96.3%), followed by BHU-B and IC 564605 (96.2%). More divergent accessions were discovered to be IC 564585, IC 564616, IC 564631, IC 564622, and IC 564630. The current investigation provides innovative knowledge to breeders on the germplasm of linseed that would be employed in subsequent research to improve linseed genotypes.